Comparison of Ice-Bank Actual Results Against Simulated Predicted Results in Carroll Refurbishment Project DKIT - Edel Donnelly (Journal of Sustainable Design and Applied Research in Innovative Engineering of the Built Environment, 2012)
This paper reviews the selection methods used in the design of an ice-bank thermal energy storage (TES) application in the Carroll’s building in Dundalk IT. The complexities of the interaction between the on- site wind turbine, existing campus load and the refurbished building meant that traditional calculation methods and programmes could not be used and specialist software had to be developed during the design process. The research reviews this tool against the actual results obtained from the operation in the building for one college term of full time use. The paper also examines the operation of the system in order to produce recommendations for its potential modification to improve its efficiency and utilisation. Simulation software is evaluated and maximum import capacity is minimised. Significant budget constraints limited the level of control and metering that could be provided for the project, and this paper demonstrates some investigative processes that were used to overcome the limitations on data availability.